TINJAUAN MASHLAHAH MURSALAH TERHADAP HAK KEPEMILIKAN KAIN SISA JAHITAN (Studi Kasus di Desa Hargomulyo Kecamatan Ngrambe Kab. Ngawi) - Neni Rahmawati; Kadenun Kadenun; Khoirul Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Ijarah contract is a contract for benefits in the form of goods or services, wages are replaced with something equivalent. Then the right of ownership is the relationship between a person and property that is determined and recognized by syara', in a way that is determined and determined by syara' or so that the property can be properly used and owned. maslahah mursalah, namely a maslahat or benefit that does not have certain arguments that justify or cancel it. As happened in Hargomulyo Village, the results of observations made by the researchers found that most tailors did not return the leftover stitches if the remaining cloth was small, if the left over seams many tailors would return it to consumers. The formulation of the problem determined is 1) What is the understanding of the tailors and consumers regarding the property rights of the remaining sewing cloth in Hargomulyo Village, Ngrambe District, Ngawi Regency? 2) What is Mashlaha Mursalah's review of the remaining stitches in Hargomulyo village, Ngrambe sub-district, Ngawi district? In this study using the field method / qualitative method (field research) because it makes direct observations while collecting data through interviews, observation and documentation. In this study using the inductive method for direct observation. The understanding of the seamstresses and consumers in Hargomulyo Village regarding the remaining sewing cloth, namely that they have the view that in general consumers never ask or ask for the remaining sewing cloth if the consumer knows that the remaining sewing cloth is small. But if there are lots of leftover stitches, new consumers ask for the remaining cloth and ask the tailor. While the understanding of the seamstress regarding the remaining stitches, that is, they have the view that in general tailors do not return the remaining stitches if the remaining is small. But if there is still a lot of cloth left, the tailor will return the remaining cloth to the consumer. Overview of Maslahah Mursalah Regarding the ownership rights of the remaining stitched cloth, that is included in the maslahah mu'tabarah because in the end the status of the remaining slightly stitched cloth is permissible when the consumer just leaves it because it is classified as matrukah goods so the tailor can take it because the previous ownership rights have been lost.